2020
DOI: 10.1007/s00408-020-00352-3
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Diaphragm Ultrasound in Reducing Time to Extubation

Abstract: Purpose Prediction of optimal timing for extubation of mechanically ventilated patients is challenging. Ultrasound measures of diaphragm thickness or diaphragm dome excursion have been used to aid in predicting extubation success or failure. The aim of this study was to determine if incorporating results of diaphragm ultrasound into usual ICU care would shorten the time to extubation. Methods We performed a prospective, randomized, controlled study at three Brown University teaching hospitals. Included subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
0
22
3
1
Order By: Relevance
“…In mechanically ventilated adults, McCool and colleagues [17] showed that the duration of mechanical ventilation was significantly shorter in patients diagnosed with normal diaphragmatic function as assessed by ultrasound measurement of diaphragmatic thickness and excursion. The authors stated that normal diaphragmatic function as assessed by ultrasound shows 90.9% sensitivity, 86.7% specificity, 90.9% positive predictive value, and 86.7% negative predictive value in predicting successful extubation from mechanical ventilation [17].…”
Section: Discussionmentioning
confidence: 99%
“…In mechanically ventilated adults, McCool and colleagues [17] showed that the duration of mechanical ventilation was significantly shorter in patients diagnosed with normal diaphragmatic function as assessed by ultrasound measurement of diaphragmatic thickness and excursion. The authors stated that normal diaphragmatic function as assessed by ultrasound shows 90.9% sensitivity, 86.7% specificity, 90.9% positive predictive value, and 86.7% negative predictive value in predicting successful extubation from mechanical ventilation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that ultrasonographic detection of the diaphragm is feasible, reproducible, and highly reliable [ 10 , 11 ]. Recently, US measurement of the diaphragm has been suggested to be valuable for predicting the optimal time for extubation in mechanically ventilated patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with diaphragm dysfunction documented with ultrasound, spontaneous breathing trial (SBT) must be cautious, and CPAP (continuous positive airway pressure) can be proposed to support the respiratory status after extubation. The use of diaphragm ultrasound may reduce the time to extubation, according to a recent randomized trial [55]. In fact, using a cut-off of diaphragm TF ≥ 30% in ICU patients undergoing SBT, Mc Cool et al [55] reported a significant reduction of the time from ultrasound to extubation in an interventional group in comparison with a group receiving usual care.…”
Section: Discussionmentioning
confidence: 99%